2012
DOI: 10.1186/1471-2164-13-345
|View full text |Cite
|
Sign up to set email alerts
|

Microbial transformation from normal oral microbiota to acute endodontic infections

Abstract: Background: Endodontic infections are a leading cause of oro-facial pain and tooth loss in western countries, and may lead to severe life-threatening infections. These infections are polymicrobial with high bacterial diversity. Understanding the spatial transition of microbiota from normal oral cavities through the infected root canal to the acute periapical abscess can improve our knowledge of the pathogenesis of endodontic infections and lead to more effective treatment. We obtained samples from the oral cav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(108 citation statements)
references
References 36 publications
(50 reference statements)
5
93
0
8
Order By: Relevance
“…The overall diversity of abscesses as revealed by pyrosequencing was much higher than previously reported. Most of these findings were confirmed by another study using pyrosequencing, which revealed representatives of 11 phyla and Fusobacterium as the most abundant genus (92).…”
Section: Microbial Diversity In Acute Apical Abscessesmentioning
confidence: 60%
See 3 more Smart Citations
“…The overall diversity of abscesses as revealed by pyrosequencing was much higher than previously reported. Most of these findings were confirmed by another study using pyrosequencing, which revealed representatives of 11 phyla and Fusobacterium as the most abundant genus (92).…”
Section: Microbial Diversity In Acute Apical Abscessesmentioning
confidence: 60%
“…Abscesses are polymicrobial infections for which culture studies have reported a mean number of species ranging from 2 to 8.5 per pus specimen (41-43, 45, 46, 48, 49, 96, 97, 182), while molecular studies have revealed a mean of 12 to 18 species/phylotypes per case (83,95). Findings from pyrosequencing studies suggest that these numbers can be much higher (91,92). What has become evident from most studies comparing acute apical abscesses and asymptomatic endodontic infections is that there are different dominant species in the communities, and the former are usually characterized by a significantly higher species richness than that of the latter (83,91,95,159).…”
Section: Bacterial Interactions Resulting In Collective Pathogenicitymentioning
confidence: 99%
See 2 more Smart Citations
“…Coribacteriales, a member of the gram-positive phylum Actinobacteria, were increased in the COPD and LLQ analyses. This increase was extended down to the genus level: Atopobium, a vaginal commensal and member of the oral flora [21] and Cryptobacterium, a cause of dental abscess [22]. Two orders in the grampositive phylum Firmicutes were differentially abundant.…”
Section: Resultsmentioning
confidence: 97%